Population trajectory and stressors of Acropora palmata sites in the Florida Keys - Neely, Karen L.; Macaulay, Kevin A.; Lunz, Kate S. (Frontiers in Marine Science, 2022)
The decline of elkhorn coral, Acropora palmata, has been ongoing for decades, but the causes of decline and the resulting population status continue to be topics of study. Past efforts to categorize stressors have ranged from spatially and/or temporally focused efforts that detect local stressors but may miss broader patterns to meta-analyses that identify large-scale trends but may not account for finer-scale variability. We here conduct an analysis of sites surveyed across five years (2010-2015) and much of the Florida Reef Tract in order to look at large-scale patterns while also accounting for site, habitat, seasonal, and annual variability. Through fate-tracking across nine sites, we assess trends in total tissue amount, fragmentation and fragment survival, and prevalence and severity of stressors. Acute stressors included severe bleaching events and spikes in disease prevalence, while chronic stressors were dominated by corallivorous snail predation. Four of nine survey sites experienced near total declines in population over the survey period, but the timing and cause of each differed, even among sites within a few kilometers of each other. There were notable differences in the prevalence and severity of stressors between forereef and backreef sites. We conclude that generalizing the population trajectories and stressors of A. palmata can misrepresent the conditions at individual sites. We also conclude that the forereef and backreef environments examined here differ in their stressors, and that habitat should be identified as a variable of interest in assessing A. palmata trajectories. We use this information to speculate that the remaining population of A. palmata within Dry Tortugas National Park may have survived as a result of its unique backreef geography.